The Cotransplantation of Olfactory Ensheathing Cells with Bone Marrow Mesenchymal Stem Cells Exerts Antiapoptotic Effects in Adult Rats after Spinal Cord Injury - Shifeng Wu; Guanqun Cui; Hua Shao; Zhongjun Du; Jack C. Ng; Cheng Peng (Hindawi Limited, 2015)
The mechanisms behind the repairing effects of the cotransplantation of olfactory ensheathing cells (OECs) with bone marrow mesenchymal stromal cells (BMSCs) have not been fully understood. Therefore, we investigated the effects of the cotransplantation of OECs with BMSCs on antiapoptotic effects in adult rats for which the models of SCI are induced. We examined the changes in body weight, histopathological changes, apoptosis, and the expressions of apoptosis-related proteins after 14 days and 28 days after transplantation. We also assessed animal locomotion using BBB test. We found that treatment with OECs and BMSCs had a remissive effect on behavioral outcome and histopathological changes induced SCI. Furthermore, we observed the significant antiapoptotic effect on cotransplant treated group. In addition, cotransplantation of OECs with BMSCs was found to have more significant repairing effect than that of OECs or BMSCs alone. Furthermore, the recovery of hind limb could be related to antiapoptotic effect of OECs and BMSCs through downregulating the apoptotic pathways. Finally, our data suggested the cotransplantation of OECs with BMSCs holds promise for a potential cure after SCI through the ability to incorporate into the spinal cord.